Microsporogenesis, microgametogenesis, and pollen grain morphology of Fouquieria fasciculata (Fouquieriaceae, Ericales) - Fabiola Soto-Trejo; Sergio Zamudio-Ruiz; Silvia Espinosa-Matías (Botan‪ical Sciences, 2023)
Background: Embryology of the male reproductive structures in Fouquieriaceae has been poorly studied. The ontogeny of the anther wall, microsporogenesis, microgametogenesis, and pollen morphology were described in detail for Fouquieria fasciculata.